Bancassurance Business In India: Reviews From The Perception of Bank Employees - Kaur, Navdeep; Kaur, Ravneet (Gyan Management Journal, 2024)
Over the past one decade, financial market of India has witnessed aremarkable change in banking and insurance sector. The insurancecompany sells insurance related products with the help of bank saleschannel. When these two big financial institutions join togetherwith a mutual purpose, it gives birth to “Bancassurance”. The successof bancassurance business hinges on the employees’ attitude whoexecutes bancassurance practices in banks. The purpose of thestudy is to provide better insights of the employees’ perspective onbancassurance. The study reviewed various research papers taken fromrelevant research databases. Further, study explains the analysis ofemployee’s perspective under three dimensions i.e. motivating factorsof bancassurance, perceived benefits of bancassurance and problemsof bancassurance. The results of the study revealed that positiveperception of employees plays a vital role in success of bancassuranceand enhances the excellent customer’s relationship.
Keywords: HRMS; Blowfish; algorithm; Data; Multithreading; and management